Report on living liver donor risk and outcomes: Single center experience - Jamilya Saparbay; Abylaikhan Sharmenov; Chokhan Aytbayev; Assylmurat Zhumukov; Bekkhozha Yeskendirov; Zhanat Spatayev; Asan Zhexembayev (Transplantation Reports)
Introduction Donor hepatectomy is considered as a major surgical procedure and can lead to severe complications. Since 2012, 64 deceased donor liver transplantation (DDLT) and 420 living donor liver transplantation were performed in Kazakhstan. Efforts to increase deceased liver donation have shown no success. In this study, we analyzed major and minor complications among living liver donor after left and right liver lobe donation, performed in our center. Patients and methods This retrospective study was conducted in compliance with the principles of the Declaration of Helsinki. The Local Ethics Committee of NROC approved this study. All data regarding living liver donors, who underwent donor hepatectomy between 2016 and 2023 were retrieved from electronic records. Results The mean age of living donors was 32 years (range 18–61).Male/female ratio was 51(70.8 %)/21(29.2). 4 left liver grafts;2 left lateral grafts and 66 right liver grafts. Bile leak occurred in 9 cases (12.5 %), 2 cases of bile leakage in living donors required surgery (Clavien grade III). Bleeding totally occurred in 3 living donors (4.2 %), in 2 cases it required surgery. PHLF occurred in 15(20.8 %) cases after right liver lobe donation. No living liver donor death was encountered in our study. Conclusions Our experience in living donor hepatectomy was not fully safe procedure. However, complication occurrence was comparable with other reports from transplant centers.